Deceptive and Subliminal Food Advertising - Csorba, Luiela Magdalena (Mediterranean Journal of Social Sciences, 2011)
The purpose of advertising is to make sure that people know about the range of products and services that areavailable on the market. It is the interest of the manufacturers and retailers to make as many consumers as possible aware oftheir products or services. But, it is important to ensure that ads meet certain standards, particularly relating legal and ethicalrequirements, because consumers do not always have sufficient knowledge to decipher the messages in advertising, to detectthe exaggerations or the possible frauds. They, therefore, need to be protected from the incorrect or misleading ads. Advertisingcan encourage the people to over - consume, which is bad for the consumers’ wallet, for the environment and for the sustainabledevelopment. But, if the deceptive and subliminal advertising may harm the security of the children, it means that urgentmeasures must be taken to protect this special social class.